Diseño cálculo y simulación de una máquina trituradora de bolsas plásticas - Sotaquira Robles, Nelson Arnulfo; Cely Salamanca, Franklin Yair (Universidad Antonio Nariño, 2023)
To ensure efficiency in the selection and classification stages of a waste treatment plant, these must be outside the bag or packaging that contains them. The proposed bag-opening machine must be a machine specifically designed to break and empty bags of all sizes that reach both urban waste treatment plants and packaging and waste classification plants